Legal Standing of the Organization of Islamic Cooperation for Indonesian Migrant Workers - Towadi, Mellisa; Supriyanto, Agustinus (Indonesian Journal of Advocacy and Legal Services, 2020)
This manuscript aims to analyze the extent to which the role, the tendency, the influence of the Organization of Islamic Cooperation (OIC) to protect Indonesian migrant workers in that member states. The analysis was carried out uses a juridical normative method, and resulted in that OIC to the protection of Indonesian migrant workers confirmed has a strong capacity to solve migrant workers' problems among its member states. In this case implementation of the employment policies issued by the OIC are a form of empowerment resources migrant workers through indirect protection (through education, training, dissemination, research, and development) that has prospects good enough for Indonesia to protect migrant workers although not significant.